Trapped fourth ventricle: a rare complication in children after supratentorial CSF shunting - El Damaty, Ahmed; Eltanahy, Ahmed; Unterberg, Andreas; Bächli, Heidi (Child's nervous system, 2020)
Trapped fourth ventricle (TFV) is a well-identified problem in hydrocephalic children. Patients with post-hemorrhagic hydrocephalus (PHH) are mostly affected. We tried to find out predisposing factors and describe clinical findings to early diagnose TFV and manage it.
Gesehen am 31.08.2021